Training leaders in reproductive health of women. - Ludmir, Abraham (2015)
The Peruvian Society of Obstetrics and Gynecology through its standing committee proposes training leaders in this project in order to deepen and broaden knowledge and skills in the specialty of ginecoobtetricia especially in the fields of perinatology, obstetrics and gynecology Human Reproduction and Oncology gynecological. It is proposed to develop an annual program that offers the opportunity to young doctors who have completed their residentado of obstetrics and gynecology or ginecoobstetras doctors who are practicing in a hospital MOH and IPSS, who through a selection process to obtain grants to develop knowledge , skills, and leadership responsibilities in the fields of human reproduction, perinatology and oncology, for which they must be assigned to a teaching hospital prequalified for a year.